Simulation of Reduced Switch Nine-level Multilevel Inverter with SHEPWM using Salp Swarm Algorithm - Arshad, Mohd Hafiz; Ismail, Baharuddin; Aihsan, Muhammad Zaid; Mat Isa, Zainuddin; Charin, Chanuri (Semarak International Journal of Electronic System Engineering, 2025)
Harmonic contents in any type of inverter output voltage, particularly at the lower order harmonic, have a significant impact on the operation of various appliances and the system's reliability. The issue in this design is to determine the optimal switching angles for the modulation switching technique which used control the switching devices. Because of the capacity to suppress any single individual harmonic, this system requires the Selective Harmonic Elimination Pulse Width Modulation (SHEPWM) switching mechanism. Due to the efficacy of the metaheuristic optimization algorithm, a recent Bio-inspired Intelligent Algorithms (BIAs), Salp Swarm Algorithm (SSA), will be evaluated for use in the power electronic area as an angle provider for this system. As a result, this work provides a proposed topology with SHEPWM using the SSA. The proposed circuit was modelled and simulated using PSIM software. Total Harmonic Distortion (THD) results will be chosen for modulation 0.56 and 0.83 due to the best global optima performance. The results demonstrate that the fifth, seventh, and eleventh order harmonics have been completely eradicated.